Diagnostic potential and future directions of biomarkers in gingival crevicular fluid and saliva of periodontal diseases: Review of the current evidence - Ghallab, Noha Ayman (Archives of oral biology, 2018)
•Oral biomarkers can be used as an adjunctive method for diagnosis & monitoring of periodontal disease progression.•No clinical or laboratory test is routinely employed in monitoring patients with periodontal disease.•High-quality research designs targeting sensitivity & specificity are still warranted to recognize GCF & salivary biomarkers with the clinical utility to identify current & future periodontal disease activity.•Future developments in proteomic analysis will pave the way for providing individual “signatures” for risk of periodontal disease. The holy grail of biomarker research in periodontology is to develop a high impact diagnostics which have a significant impact on clinical decision-making, patient outcomes and healthcare providers. In the field of periodontal diagnostics, oral fluid-based biomarkers have been studied mainly in the gingival crevicular fluid (GCF) and saliva. A literature search was performed using the Cochrane library and PubMed databases from 2000 to January 2017. Currently, there are more than 90 different components in the GCF that have been investigated as diagnostic and prognostic markers of periodontal disease progression involving; inflammatory mediators, markers of oxidative stress, host-derived enzymes, tissue-breakdown products and mediators of bone homeostasis. Furthermore, various biomarkers in saliva have been proposed which reveal a promising outlook for saliva as a key diagnostic medium for periodontal disease. Recent systematic reviews with high value of evidence have shown that potential salivary biomarkers can provide important complimentary diagnostic information and can be used as tests for screening diagnosis, prognosis and predicting periodontal disease progression. Future developments in proteomic analysis and personalized medicine will pave the way allowing novel diagnostic tools. Still, the application into the field of dentistry will depend on how practitioners will apply this into their daily clinical practice. Still, the application into the field of dentistry will depend on how practitioners will apply this into their daily clinical practice.